Energy detector assisted by geolocation database scheme utilizing radar bands - Mohamoud, Mohamoud Ali; Elsheikh, Elsheikh Mohamed Ahmed; Habaebi, Mohamed Hadi (Asian Research Publishing Network (ARPN), 2015)
Cognitive Radio (CR) is an intelligent method for opportunistic access of idle resources and a solution for spectrum resources scarcity. In this article a new technique for spectrum access is proposed. This technique combines energy detector with geolocation database. The proposed technique is employed in radar bands of (960-1400 MHz, 2.7-3.6 GHz and 5-5.85 GHz). These bands occupy quite large bandwidth and they are utilized only about 5% of the time. The new proposed technique is expected to solve the problem of hidden receivers faced by energy detector. It also poses a solution for the static nature of geolocation database method. It minimizes the interference caused by secondary users by improving the probability of detection. Furthermore, it improves the spectrum utilization through the improvement of false alarm probability.